Validez de los actos o contratos contenidos en escrituras públicas que han sido constituidas legalmente. - Rocafuerte Tipan, Christian Wladimir (Machala : Universidad Técnica de Machala, 2018)
Public deeds are instruments whose validity and suitability are decisive for the development of many acts and contracts with which people manage their assets. A well-executed writing, both formally and in its content, is guarantees for the contracting parties. In the present investigation the acts and contracts, their validity, their budgets have been developed as an object of study, and as a main objective we set out to determine if in the process taken as a central point of discussion, the Judge who resolved the case correctly differentiated the public deed of the act or contract contained in this. Several variables were proposed on this objective, the same ones that were discussed through the opinions of various authors who dealt with the subject on the subject, as well as the jurisprudence that was reviewed, which is why we conclude that they are two different things. public deed, whose validity or legality, are independent of the validity or legality of the act or contract that is contained, so that the deed may be valid, but the contract may be invalid by not complying with the legal requirements for the required effect. The requirements for the validity of contracts are regulated in the fourth book of the civil code, while the requirements for the validity of public deeds are developed in the notarial law. When we started selecting the case study, we appreciated that there was a problem of great legal relevance, since the judge declared a nullity suit for public deed, in which the plaintiff alleged that the contract had been concluded with a vice in the consent, which is a requirement of validity of the contracts, that is, that the plaintiff was wrong to request the nullity of the deed, when what he had to actually request was the nullity of the contract contained in the deed, and thus the Judge had to decide on the merits of the case. The requirements for the validity of contracts are: capacity, free consent, lawful object and lawful cause. On the consent we have that it is free as long as it is not vitiated, and are possible vices of consent, error, force and fraud. The need to establish a sufficient dogmatic structure to be able to clarify the object pursued, also required us to propose as an objective, to differentiate error classes as vice of consent, since the plaintiff alleged an error in the species, which we actually conclude, is a true vice of consent and to be present as in fact happened in the case put to the consent of the Judge, existed, but this is not enough for the Judge of the reason to the claimant, but must be proposed correctly the claim. The process of nullity of the act or contract contained in a public deed, is an ordinary process, it is very complex, since it must be very technical to propose a claim and accompany the evidence of nullity that is alleged, much more if what it is alleged is a vice in the consent, since not only must prove that the species has a fault, but the defendant did not know of its existence at the time of conclusion of the contract.
Public deeds are instruments whose validity and suitability are decisive for the development of many acts and contracts with which people manage their assets. A well-executed writing, both formally and in its content, is guarantees for the contracting parties. In the present investigation the acts and contracts, their validity, their budgets have been developed as an object of study, and as a main objective we set out to determine if in the process taken as a central point of discussion, the Judge who resolved the case correctly differentiated the public deed of the act or contract contained in this. Several variables were proposed on this objective, the same ones that were discussed through the opinions of various authors who dealt with the subject on the subject, as well as the jurisprudence that was reviewed, which is why we conclude that they are two different things. public deed, whose validity or legality, are independent of the validity or legality of the act or contract that is contained, so that the deed may be valid, but the contract may be invalid by not complying with the legal requirements for the required effect. The requirements for the validity of contracts are regulated in the fourth book of the civil code, while the requirements for the validity of public deeds are developed in the notarial law. When we started selecting the case study, we appreciated that there was a problem of great legal relevance, since the judge declared a nullity suit for public deed, in which the plaintiff alleged that the contract had been concluded with a vice in the consent, which is a requirement of validity of the contracts, that is, that the plaintiff was wrong to request the nullity of the deed, when what he had to actually request was the nullity of the contract contained in the deed, and thus the Judge had to decide on the merits of the case. The requirements for the validity of contracts are: capacity, free consent, lawful object and lawful cause. On the consent we have that it is free as long as it is not vitiated, and are possible vices of consent, error, force and fraud. The need to establish a sufficient dogmatic structure to be able to clarify the object pursued, also required us to propose as an objective, to differentiate error classes as vice of consent, since the plaintiff alleged an error in the species, which we actually conclude, is a true vice of consent and to be present as in fact happened in the case put to the consent of the Judge, existed, but this is not enough for the Judge of the reason to the claimant, but must be proposed correctly the claim. The process of nullity of the act or contract contained in a public deed, is an ordinary process, it is very complex, since it must be very technical to propose a claim and accompany the evidence of nullity that is alleged, much more if what it is alleged is a vice in the consent, since not only must prove that the species has a fault, but the defendant did not know of its existence at the time of conclusion of the contract.
Keywords: VALIDEZ; ACTO; CONTRATO; ESCRITURA